Conjugated Oligoelectrolytes for Long‐Term Tumor Tracking with Incremental NIR‐II Emission. Issue 20 (18th April 2022) - Zhou, Cheng; Li, Zeshun; Zhu, Ziyue; Chia, Geraldine W. N.; Mikhailovsky, Alexander; Vázquez, Ricardo Javier; Chan, Samuel J. W.; Li, Kai; Liu, Bin; Bazan, Guillermo C.
Abstract: The design and synthesis of the near‐infrared (NIR)‐II emissive conjugated oligoelectrolyte COE‐BBT are reported. COE‐BBT has a solubility in aqueous media greater than 50 mg mL −1, low toxicity, and a propensity to intercalate lipid bilayers, wherein it exhibits a higher emission quantum yield relative to aqueous media. Addition of COE‐BBT to cells provides two emission channels, at ≈500 and ≈1020 nm, depending on the excitation wavelength, which facilitates in vitro confocal microscopy and in vivo animal imaging. The NIR‐II emission of COE‐BBT is used to track intracranial and subcutaneous tumor progression in mice. Of relevance is that the total NIR‐II intensity increases over time. This phenomenon is attributed to a progressive attenuation of a COE‐BBT self‐quenching effect within the cells due to the expected dye dilution per cell as the tumor proliferates. Abstract : A near‐infrared‐II membrane‐intercalating conjugated oligoelectrolyte (COE) is designed and synthesized for long‐term monitoring of tumor progression in mice, as a proof‐of‐concept for noninvasive in vivo cell tracking. In contrast to current exogenous probes, the COE emission intensity increases with tumor growth, thereby harnessing advantages of both direct‐labeling and indirect‐labeling methods.